2020
DOI: 10.1016/j.heliyon.2020.e03492
|View full text |Cite
|
Sign up to set email alerts
|

The hydroxyl moiety on carbon one (C1) in the monoterpene nucleus of thymol is indispensable for anti-bacterial effect of thymol

Abstract: Background: Thymol, a natural monoterpene phenol is not only relevant clinically as an anti-microbial, antioxidant and anti-inflammatory agent but also holds the prospect as a natural template for pharmaceutical semisynthesis of therapeutic agents. It is a major component of essential oils from many plants. Evidence abound linking overall bioactivity of thymol to its monoterpene nucleus, specifically, the hydroxyl (-OH) substituent on carbon number one (C1) on the monoterpene nucleus. Other studies have posite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…The substitution of chlorine on the carbon-4 positions of the thymol nucleus played vital role that afforded the superior activity of compounds 6,7, 8, 9 and 10 over the other compounds and the parent compound, thymol. The hydroxyl moiety on thymol also did confer an activity as thymol showed a mean zone of inhibition against all the bacteria with mean zone of inhibition ranging between 13.7 and 2.7 mm which confirms earlier results that [ 15 ], the hydroxyl group of thymol is indispensable for its antimicrobial activity.
Figure 1 Mean zones of inhibition (mm) of compounds 1–10 (100 μg/ml) against tested bacteria.
…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The substitution of chlorine on the carbon-4 positions of the thymol nucleus played vital role that afforded the superior activity of compounds 6,7, 8, 9 and 10 over the other compounds and the parent compound, thymol. The hydroxyl moiety on thymol also did confer an activity as thymol showed a mean zone of inhibition against all the bacteria with mean zone of inhibition ranging between 13.7 and 2.7 mm which confirms earlier results that [ 15 ], the hydroxyl group of thymol is indispensable for its antimicrobial activity.
Figure 1 Mean zones of inhibition (mm) of compounds 1–10 (100 μg/ml) against tested bacteria.
…”
Section: Resultssupporting
confidence: 87%
“…The chemical modification of the hydroxy (–OH) group into its ether and ester derivatives afforded new lead compounds found to be effective against Helicobacter pylori infection to prevent the occurrence of severe gastric disease conditions [ 14 ]. A recent study also showed that the hydroxyl functional group of thymol was indispensable for its anti-bacterial effect [ 15 ]. Modification of the hydroxy group into ester and ether derivatives resulted in low anti-bacterial activities on the following organisms Staphylococcus aureus (Gram positive), Escherichia coli (Gram negative) and Pseudomonas aeruginosa (Gram negative) compared to the parent compound, thymol [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm is quiet common in poorer tropical countries of the world, where most people rely on herbal medicine to meet their primary health care needs [8]. Also, this may probably affirm the usual assertion that use of herbs predates modern medicine and that natural products continue to serve as templates for pharmaceutical semisynthesis of new drugs [10] including antidiabetic agents. Importantly, these herbs and herb-derived therapies are used as adjunctive therapy in a manner that reflects the belief systems and ethnobotanical heritage of most local communities across Afro-Asian regions of the world.…”
Section: Introductionmentioning
confidence: 83%
“…Additionally, the inhibitory effect of Thy on S. putrefaciens showed a positive correlation with the concentration within a certain concentration range. Boye et al (2020) assessed the antimicrobial activity of 12 thymol derivatives against pure clinical isolates, including Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. They discovered that thymol exhibited a broad-spectrum antibacterial effect, resulting in concentration-dependent growth inhibition, primarily attributed to the hydroxyl moiety on the C1 position of the monoterpenoid core.…”
Section: Mic and Mbcmentioning
confidence: 99%